2015
DOI: 10.1037/lhb0000113
|View full text |Cite
|
Sign up to set email alerts
|

A field evaluation of the Eye-Closure Interview with witnesses of serious crimes.

Abstract: research shows that eye-closure during memory retrieval improves both the amount and the factual accuracy of memory reports about witnessed events. Based on these findings, we developed the Eye-Closure Interview, and examined its feasibility (in terms of compliance with the instructions) and effectiveness (in terms of the quantity and quality of reported information) in eyewitness interviews conducted by the South African Police Service. Police interviewers from the Facial Identification Unit were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
(56 reference statements)
0
19
0
1
Order By: Relevance
“…It would therefore be important to extend our findings to free-recall tasks, which would furthermore provide data on the amount of time and effort expended by witnesses in recounting their memories. Finally, our Eyes-Closed participants were told that eyeclosure should assist their remembering, whereas participants in prior studies were either told nothing, or given a decoy justification ('it may help you to relax'; Vredeveldt et al, 2015). We have argued that disclosing the purpose realistically characterizes the eyeclosure technique; nevertheless it would be useful to explore whether witnesses' understanding of the purpose of closing their eyes affects its benefits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It would therefore be important to extend our findings to free-recall tasks, which would furthermore provide data on the amount of time and effort expended by witnesses in recounting their memories. Finally, our Eyes-Closed participants were told that eyeclosure should assist their remembering, whereas participants in prior studies were either told nothing, or given a decoy justification ('it may help you to relax'; Vredeveldt et al, 2015). We have argued that disclosing the purpose realistically characterizes the eyeclosure technique; nevertheless it would be useful to explore whether witnesses' understanding of the purpose of closing their eyes affects its benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Vredeveldt and colleagues have gathered evidence in favour of modality-specific processes. In particular, when focusing solely on witnesses' reporting of highly specific, fine-grained details, they found that eyeclosure selectively enhances visual recall (e.g., Vredeveldt & Penrod, 2013;Vredeveldt et al, 2015). Together these findings point to both modality-specific and generalized cognitive processes underpinning eyeclosure effects.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…All panel members had extensive experience with drug cases in which observations by surveillance detectives typically play a role. We showed our video to each panel member individually and asked: ‘What information in this video would you consider to be most important from the perspective of a criminal investigation?’ (for similar approaches, see Roberts & Higham, ; Vredeveldt, Tredoux, Nortje, et al ., ). Each panel member provided as many responses as they wished and ordered their responses in terms of priority.…”
Section: Methodsmentioning
confidence: 99%